2018
DOI: 10.1111/jfb.13687
|View full text |Cite
|
Sign up to set email alerts
|

Otolith development in wild populations of stickleback: Jones & Hynes method does not apply to most populations

Abstract: This paper critiques Jones & Hynes (1950) findings by analysing sequential samples of otoliths from three wild populations of Gasterosteus aculeatus from North Uist, Scotland and Nottingham, England. Contrary to Jones & Hynes (1950), but coincident with the finding of later researchers, our results showed that no true translucent ring formed in the otolith of G. aculeatus during their first summer. The first translucent ring was probably starting to be formed by the end of summer and was completed by the end o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 35 publications
(124 reference statements)
1
4
0
Order By: Relevance
“…Following this growth phase, a narrow transparent zone develops and remains to be the outermost until the next summer (growing) season. This pattern of otolith formation in northern G. aculeatus is different from that described earlier (Jones & Hynes, ), but agrees with later observations (Allen & Wootton, ; Singkam & MacColl, ; Tiller, ).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Following this growth phase, a narrow transparent zone develops and remains to be the outermost until the next summer (growing) season. This pattern of otolith formation in northern G. aculeatus is different from that described earlier (Jones & Hynes, ), but agrees with later observations (Allen & Wootton, ; Singkam & MacColl, ; Tiller, ).…”
Section: Discussionsupporting
confidence: 83%
“…A combination of factors such as availability of reference material of known age (otoliths, gill covers), inherent difficulty of reading annuli and existing knowledge about their formation could have led to differences among readers in the current study. Indeed, otoliths were considered by readers as convenient structures for age estimation due to the presence of reference yearling otolith photos (Figure ), relatively clear annuli and available information on their formation (Allen & Wootton, ; Jones & Hynes, ; Singkam & MacColl, ; Tiller, ). The repeatability for otoliths could have been even higher if not for extra markings observed in the central part of larger otoliths, which were absent in yearlings (Figure a,b vs .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, these three species may have experienced similar seasonal environmental changes. Several studies have reported sub‐annual rings on the otoliths of the three‐spined stickleback ( Gasterosteus aculeatus ), which belongs to the same family as Pungitius , but there is disagreement as to when these sub‐annual rings are formed (Singkam & MacColl, 2018 ). SingKam and MacColl ( 2018 ) concluded that the first opaque rings are formed between birth and the end of the first summer, when food is abundant; the first translucent rings are formed between the end of the first summer and the end of the first winter; and the second opaque rings are formed after the spring of the second year.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported sub‐annual rings on the otoliths of the three‐spined stickleback ( Gasterosteus aculeatus ), which belongs to the same family as Pungitius , but there is disagreement as to when these sub‐annual rings are formed (Singkam & MacColl, 2018 ). SingKam and MacColl ( 2018 ) concluded that the first opaque rings are formed between birth and the end of the first summer, when food is abundant; the first translucent rings are formed between the end of the first summer and the end of the first winter; and the second opaque rings are formed after the spring of the second year. By applying their interpretation to our results, we can infer that drilling area 1 formed early in the first year, drilling area 2 formed late in the first year, drilling area 3 formed in the second year, and drilling area 4 formed during the third year.…”
Section: Discussionmentioning
confidence: 99%